Musical training of coaches in aesthetic-oriented sports - Irina Belenkaya (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to justify theoretically the need for musical training of coaches in aesthetic-oriented sports. Material & Methods: theoretical analysis and generalization of scientific and methodological literature, pedagogical supervision. Results: the main directions of musical training of coaches in aesthetic-orientated sports were reviewed. It was discovered that in these types of sports coaches must have specific musical and rhythmic motor skills involving the use of musical accompaniment as a methodological technique for training sessions. The means of music and rhythmic education, which facilitate effective musical training of coaches in aesthetic-oriented sports, were determined. Conclusions: the necessity of improving the teaching methods of the subject "music and rhythmic education" as part of the musical training of coaches in aesthetic-orientated sports, was theoretically justified.